Biochemical Investigation of Serum Iron Level in Water Buffaloes in Three Regions of Babylon, Iraq - Kadhim AL-Wasmee, Ahmed Kareem; Salman, Sufyan Saleh (Journal of Buffalo Science, 2025)
Buffalo is a multipurpose ruminant that can adjust to a variety of environmental conditions. The quality of soil and forages determines iron (Fe) availability to ruminants. The objectives of this study were to examine how serum Fe levels and related physiological and biochemical indices in water buffaloes affected by regional differences in Fe levels of soil and forages from three regions (South, Middle, and North) of the Babylon Province, Iraq. A total of 180 water buffaloes of various ages and sexes were randomly selected from three regions (South, Middle, and North) of Babylon Province, Iraq. All buffaloes were clinically examined. Then, fecal samples for parasitology examination and blood samples were collected for use in hematology and biochemical analysis.Soil and forage samples were collected and analyzed for Fe levels using atomic absorption spectrophotometry (AAS). Data were statistically evaluated by using SPSS. Our study revealed a significant regional variation in soil Fe levels, highest in the South, moderate in the Middle, and lowest in the North. Forage Fe content varied by type and region, with decreased Fe levels in barley grasses in the North region, while other regions showed Fe levels within the normal range. The Fe levels in alfalfa grass in the North region declined, while Fe levels in the South and Middle regions were within normal range. The Fe level in fresh rice straw decreased in the South, Middle, and North regions. Markedly, 96.11% of buffaloes had serum Fe levels below the normal range. The body temperature was within normal range, while respiratory and pulse rates were increased. (92.22%), (0%), and (2.22%) of buffaloes had ferritin, transferrin, and total iron binding capacity (TIBC) below normal levels, respectively; and (6.11%), (3.33%), and (0%) of buffaloes had normal levels, respectively; and (1.66%), (96.66%), and (97.77%) of buffaloes had higher than normal levels, respectively. (98.88%), (95.55%), and (98.88%) of buffaloes had red blood cells (RBCs), hemoglobin (Hb), and hematocrit (Hct) below normal levels, respectively; (1.12%), (4.44%), and (1.12%) of buffaloes had normal levels, respectively; and (0%) of buffaloes had greater than normal levels. To the best of our knowledge, this is the first study in Babylon province, Iraq, to identify how the serum Fe levels of buffaloes are affected by the regional differences in levels of Fe in soil and three different types of forages.